A Population based Study on Self Medication Practice in Pakistan - Khan, Kamran; Zaman, Aqsa; Khurshid Hashmi, Furqan; Khan, Rizwan (AL-Kindy College Medical Journal, 2022)
Background: The risk of antibiotics resistance (AR) increases due to excessive of antibiotics either by health care provider or by the patients. Objective: The assessment of the self-medication Practice of over the counter drugs and other prescription drugs and its associated risk factor. Subjects and Methods: Study design: A descriptive study was conducted from “20th December 2019 to 08th January 2021”. A pre validated and structured questionnaire in English and Urdu language was created to avoid language barrier including personal detail, reasons and source and knowledge about over the counter drugs and Antibiotics. Sample of the study was randomly selected. Data was analyzed by software SPSS version 22. Results: Out of n=3388 respondents, the prevalence of self -medication practice of OTC drugs and antibiotics as self – medication practice in all of the respondents is 88% and 85.9% respectively. Knowledge of the respondents about the use of the antibiotics as well as side effects of antibiotics was 40.7% and 15.3% respectively. Headache, fever, cough and stomach problem were the minor ailments for which majority of OTC drugs and antibiotics used respectively. The commonly used OTC drugs and OPDEA were Paracetamol and Omeprazole. The commonly used antibiotics were Metronidazole, Amoxicillin and Clavulanic acid and Ciprofloxacin. Conclusion: Government should make policies to train pharmacist in the community for antibiotics stewardship and standard treatment guidelines through educational workshops. Our future study will be on how to minimize antimicrobial resistance in the developing countries • Conclusion: Government should make policies to train pharmacist in the community for antibiotics stewardship and standard treatment guidelines through educational workshops. Our future study will be on how to minimize antimicrobial resistance in the developing countries.